The Impact of Exemptions in the Austrian Tax Code on the Distribution of Income and the Gender Pay Gap - Berka, Christopher; Piber, Philipp (Momentum Quarterly, 2013)
Reducing inequality by means of taxation is a major concern of welfare state policies. In this context, the distribution of income between men and women is considered to be an important aspect. While most economic research focuses on gender-specific effects of government expenditures (child care), this paper points at the role of tax exemptions, which contribute to gender inequality in many countries. The Austrian tax code features several allowances that reduce the taxable base for social security contributions as well as for income taxes. We show that these exemptions, in sum, lead to redistribution of income to the top, since the regressive allowances incorporated in the Austrian tax system overcompensate for allowances aiming at low-income groups. As these exemptions disproportionally reduce the tax burden for high income earners, which are disproportionately male, we conclude that on the whole the allowances in the Austrian tax code lead to a redistribution of income from women to men.
Keywords: micro-simulations; income distribution; taxation; gender-budgeting